Control System Design for a Surface Cleaning Robot. (2nd May 2013) - Yuyi, Zhai; Yu, Zhou; Huanxin, Luo; Yunjia, Liu; Liang, Liu
Abstract This paper aims to study a control system for a surface cleaning robot and the focus of the study is the surface cleaning robot controller design. The structural framework of the propulsion control system of the surface robot is designed based on the principle of PWM speed control. The function of each module in the control system is divided and described in detail. A kind of thinking based on an AVR microprocessor and its software and hardware design proposals are presented. Through RS485 and PC communication according to the agreed protocol, the control system achieves robot forward, backward, turn and work operations by the use of a DC motor or stepper motor, and it can therefore more successfully realize the work of a surface cleaning robot.